Regularities of the Process of Democratization of Society - Demirchyan, Movses (YSU Journal of International Affairs, 2019)
The article analyzes the process of democratization of society and related problems, which are both local and global. The first are associated with the peculiarities of the cultural and historical development of this society, the second ones are associated with international experience in the application of democratic norms and institutions, as well as with different interpretations of democracy. It is argued that democratization cannot concern only society or only the state, but should take place either from the top to down or from the bottom to up, but in any case affecting all spheres of public life, starting with everyday relations and ending with politics and government. As theoretical models of crisis or problems of democratization, the concepts of “democracy deficit” and “expectations of democracy” are analyzed. These concepts reveal the negative patterns of the spread of democratic ideas and practices in the social reality.